2010
DOI: 10.1007/s11165-010-9187-0
|View full text |Cite
|
Sign up to set email alerts
|

Science Instructors’ Perceptions of the Risks of Biotechnology: Implications for Science Education

Abstract: Developing scientifically literate students who understand the socially contextualized nature of science and technology is a national focus of science education reform. Science educators' perceptions of risks and benefits of new technologies (such as biotechnology) may shape their instructional approaches. This study examined the perceived risk of biotechnology of four groups of science educators: pre-service science teachers, in-service science teachers, biology graduate teaching assistants, and biology profe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 54 publications
0
7
0
3
Order By: Relevance
“…In a previous study, we found that undergraduates in a particular field have a less nuanced understanding of the potential risks from science-related objects and activities than corresponding faculty on the field (Gardner & Jones, 2011). Numerous studies comparing science 'experts' with the general public have mirrored these results but have gone even farther in suggesting that the general public typically perceives more risk related to science than experts in certain science contexts (Slovic, 1992).…”
Section: Perception Of Risks Disgust and Attitudes Toward Microbesmentioning
confidence: 82%
“…In a previous study, we found that undergraduates in a particular field have a less nuanced understanding of the potential risks from science-related objects and activities than corresponding faculty on the field (Gardner & Jones, 2011). Numerous studies comparing science 'experts' with the general public have mirrored these results but have gone even farther in suggesting that the general public typically perceives more risk related to science than experts in certain science contexts (Slovic, 1992).…”
Section: Perception Of Risks Disgust and Attitudes Toward Microbesmentioning
confidence: 82%
“…Yet, despite these events and a general history of seismic activity, the seismic pattern described may be the reason for a general lack of concern about future earthquakes within the population. In fact, risk perception is related to how each person assesses as risky a particular object or event (Garder and Jones 2011). And it is a very complex issue that does not deal only with knowledge or the number of deaths it causes (Slovic 2001;Lima 2005).…”
Section: Seismic Risk and The Main Aims Of The Studymentioning
confidence: 99%
“…Divers auteurs ont utilisé la théorie culturelle de Douglas (1992) pour analyser les perceptions des risques d'élèves et d'enseignants en science (Gardner and Jones, 2011). La théorie de Douglas (1992) reflète la polarisation sociale qui influe sur la perception du risque chez une personne.…”
Section: Emergence De La Didactique Des Questions Socialement Vives (unclassified